Procedures in Translation Taking Place in the Translation of English Medical Terms with Reference to Clinical Biochemistry - Pebri Pranata, I Putu; Udayana, I Nyoman (e-Journal of Linguistics; Vol 14 No 2 (2020): e-jl JulyDO - 10.24843/e-jl.2020.v14.i02.p06, 2020)
This study aimed at finding out the translation procedures which were applied in the translation of English Medical Terms with reference to English Medical Book entitled Clinical Biochemistry 4 th and its translation version in Indonesian entitled Biokimia Klinis Edisi 4 . The analysis of translation the procedure was based on a theory proposed by Newmark (1988) by which eighteen procedures are mentioned. Moreover, this study applied a descriptive qualitative approach. In collecting data, this study applied an observation method by reading Clinical Biochemistry and its translation Biokimia Klinis comprehensively to collect the required data i.e. the medical terms and their translation. Furthermore, this study applied descriptive qualitative method in terms of analyzing data. The method was implemented by providing an explanation of the translation procedures. Moreover, the formal and informal methods were implemented in presenting the data. The formal method is indicated by the use of the table where the term and its translation were placed and differed into SL and TL. The informal method refers to the use of a descriptive explanation regarding the translation procedure. After the identification process, it was found some procedures were applied, i.e. transference, naturalization, literal, and descriptive equivalent. The dominant procedure applied was literal procedure. The contrary, descriptive equivalent was the least applied procedure. Based on the result, it can be confirmed that there was an attempt by translator in maintaining the SL words rather than considering TL words as the translation.